Assess the Impact of Strained Interpersonal Relationship with Parents on Juvenile Delinquency among Delinquent Children in Haryana: A Retrospective Case Control Study (International Journal of Nursing Education, 2019)
The objectives of the study were to assess and compare IPR score with parents among case (Delinquent children) and control (Non-delinquent children) group and to determine the association of IPR scores with selected variables among case and control group. A Non-Experimental Retrospective (Case and Control) design was used. One twenty participants were enrolled for the study. Out of which 60 delinquent children were enrolled as case group with total enumerative sampling technique and 60 school children were enrolled as control group based on matching and homogeneity with case group on convenient basis (Matching was done for age group and Homogeneity was done by enrolling only male children). Data was collected by using Modified Washington State Juvenile Court Assessment Scale for interpersonal relationship with self report technique. The findings of this study showed that the mean IPR score in case group was significantly lower than control group (70.83 Vs 74.58: t=4.74, p=0.01) which indicate control group had better IPR with parents. A significant association of IPR scores with selected variables was found i.e youth occupation (0.002) and father education (0.05) in case group and with religion(0.02), place of residence (0.008) and youth was raised by single parents(0.04) in control group. The overall prediction of IPR by the independent variables for case group was with the variability of R2= 31% (0.317) and for the control group was with the variability of R2=27% (0.271).
Keywords: Interpersonal relationship, Parents, Juvenile delinquency, Delinquent home, Delinquent children and Non delinquent children.